Evaluation of BOS Fund Accountability for Good Governance in Schools: Evaluasi Akuntabilitas Dana BOS untuk Good Governance di Sekolah - Istiqomah, Nur; Abidin, Fityan Izza Noor (Wadah Inovasi Indonesia, 2024)
This research investigates the evaluation of accountability for the management of BOS funds as an effort to realize good governance in schools. Utilizing a descriptive qualitative approach, the study involves the principal, BOS fund treasurer, school committee, and teachers directly engaged in BOS fund management. Data collection methods include interviews, observation, and documentation analysis. Findings indicate that the school's adherence to good governance principles—transparency, openness, and adherence to regulations—is commendable in managing BOS funds. This study contributes to understanding the effective implementation of governance principles in educational fund management, suggesting implications for policy and practice in school financial management and accountability.